CHOLESTEROL CRYSTAL EMBOLISM AS THE REASON OF ACUTE NON-OCCLUSIVE MESENTERIC ISCHEMIA AFTER INFRARENAL AORTIC ANEURISM REPAIR - N. A. Yaitsky; A. Ya. Bedrov; A. A. Moiseev; A. A. Vraby; A. A. Afanasyev; A. N. Morozov (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. According to the analytical data, the acute non-occlusive mesenteric ischemia after infrarenal aortic aneurism repair occurs in 0.2–1 % of cases. This complication is difficult to diagnose and associated with unfavorable prognosis and high mortality. MATERIAL AND METHODS. The retrospective analysis included 112 case histories of patients with infrarenal aortic aneurism repair in the period from 2007 to 2017. RESULTS. During the early postoperative period, 2 patients (1.8 %) had an acute non-occlusive mesenteric ischemia with lethal outcome. In these cases, the complication developed with safety patency of main mesenteric arteries and was followed by developing early multiorgan failure and thrombocytopenia. The autopsy showed generalized atherosclerosis, infarctions of kidneys, spleen and liver, caused by cholesterol crystal embolism of microvascular bed, which was found after histological research. CONCLUSION. The clinical presentation of acute non-occlusive mesenteric ischemia after infrarenal aortic aneurism repair is low-specific. One of the etiological factors of this complication is cholesterol crystal embolism in microvascular bed of visceral arteries